Gulf War Veterans : Measuring Health. - Hernandez, Lyla M. (National Academies Press, 1999)
This study, sponsored by the Institute of Medicine, presents recommendations for researching the general health of Gulf War veterans. Although there is no single diagnosable illness or set of symptoms with a known etiology characterizing any set of Gulf War veterans, there does seem to be a higher prevalence of some symptoms such as fatigue, difficulty concentrating, memory loss, skin rash, headache, and muscle and joint pain. The Institute's committee recommends implementation of a research portfolio and study that they hope will answer questions about the causes of these symptoms. Annotation copyrighted by Book News Inc., Portland, OR.